Оцінка швидкості дивергентної еволюції верхніх зубів у близьких видів нічниць Myotis blythii та M. myotis (Chiroptera, Vespertilionidae) - Гхазалі, М.А.; Дзеверін І.І. (Вестник зоологии, 2010)
Большая и остроухая ночницы (Myotis blythii Tomes, 1857 и M. myotis Borkhausen, 1797) — близкородственные виды, которые разошлись около миллиона лет назад. За этот период практически не изменились размеры рудиментарных структур зубного ряда (третьего премоляра и третьего моляра), а также доля площадей жевательных поверхностей первого и второго моляров от суммарной площади всех исследованных зубов. Эволюция других структур происходила с разной скоростью. При помощи метода Линча было обнаружено, что реальные темпы эволюции исследованных структур меньше ожидаемых для признаков, которые формировались под влиянием только случайных факторов (мутаций и генетического дрейфа). Таким образом, основным фактором в эволюции двух видов был стабилизирующий отбор. Greater and lesser mouse-eared bats (Myotis blythii Tomes, 1857, M. myotis Borkhausen, 1797)are closely related species that diverged about one million years ago. Size of the vestigial structures of the toothrow (the third premolar and the third molar) and the proportion of the first and second molar areas from the total area of the studied teeth have not practically changed during that time. Other structures evolved with different rates. Using the Lynch’s method we prove that real rates of evolution are lesser than expected for the traits which were formed under the influence of solely random factors (mutations and random drift). Apparently, the stabilizing selection, was the principal factor of the evolution of the two species was stabilizing selection.